NATURAL REMEDIES VS. SYNTHETIC ANTIBIOTICS: A COMPARATIVE REVIEW (Ustozlar uchun, 2026)
As the 2026 "silent pandemic" of antimicrobial resistance (AMR) renders traditional synthetic antibiotics increasingly obsolete, this review evaluates the shifting paradigm toward natural antimicrobial alternatives. While synthetic drugs typically utilize high-precision, single-target mechanisms—allowing for rapid bacterial adaptation—natural compounds from plants and honey utilize multi-layered chemical profiles that attack pathogens via multiple simultaneous pathways. This article synthesizes recent clinical data on Manuka honey, Allicin, and plant-derived phenols, highlighting their roles not as replacements for modern medicine, but as essential synergistic partners. We conclude that the future of infection management lies in a "Hybrid Model" that combines standardized natural extracts with legacy synthetic drugs to bypass resistance and preserve the human microbiome.